HUBUNGAN KEBIASAAN SARAPAN, AKTIVITAS FISIK, KUALITAS TIDUR DAN TINGKAT STRESS DENGAN STATUS GIZI LEBIH PADA REMAJA DI SMA SEJAHTERA 1 DEPOK - Septa Muhammad Ulvina Tanjung (2020)
In Indonesia, the prevalence of overweight and obesity continues to increase. This more nutritional problem can occur at all ages including adolescent age. Adolescence is a transition from the age of children to adult age. Some factors that can cause a person has more nutritional status are genetic, physical activity, diet, stress, socio-economic, breakfast, body image, duration and quality of sleep. The purpose of this research is to know the relationship between breakfast habits, physical activity, sleep quality and stress levels with the nutritional status overweight adolescent at SMA Sejahtera 1 Depok. The design used is cross sectional and involved as many as 60 respondents randomly selected with simple random sampling technique. The analysis used is Chi-Square. Bivariate analysis test results showed that breakfast habits (p = 1,000), physical activity (p = 1,000), sleep quality (P = 0,511) and stress levels (P = 0,112). This indicates that there is no relationship between breakfast habits, physical activity, sleep quality and stress levels with nutritional status overweight adolescent in SMA Sejahtera 1 Depok.